2020
DOI: 10.1136/bmjopen-2020-039747
|View full text |Cite
|
Sign up to set email alerts
|

Development and internal validation of prognostic models to predict negative health outcomes in older patients with multimorbidity and polypharmacy in general practice

Abstract: BackgroundPolypharmacy interventions are resource-intensive and should be targeted to those at risk of negative health outcomes. Our aim was to develop and internally validate prognostic models to predict health-related quality of life (HRQoL) and the combined outcome of falls, hospitalisation, institutionalisation and nursing care needs, in older patients with multimorbidity and polypharmacy in general practices.MethodsDesign: two independent data sets, one comprising health insurance claims data (n=592 456),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…The MAI is considered to be the most reliable and valid implicit instrument to measure the appropriateness of a patient’s medication regime. The studies collected in Hanlon et al [ 39 ] demonstrated both validity and its association with relevant and specific service, in line with the results of the study by Müller et al [ 41 ]. In 1997, Schamder et al [ 42 ] found that a difference of two points was associated with differences in hospitalization and unscheduled outpatient or emergency visits.…”
Section: Discussionsupporting
confidence: 76%
“…The MAI is considered to be the most reliable and valid implicit instrument to measure the appropriateness of a patient’s medication regime. The studies collected in Hanlon et al [ 39 ] demonstrated both validity and its association with relevant and specific service, in line with the results of the study by Müller et al [ 41 ]. In 1997, Schamder et al [ 42 ] found that a difference of two points was associated with differences in hospitalization and unscheduled outpatient or emergency visits.…”
Section: Discussionsupporting
confidence: 76%
“…The current study was designed as a controlled, cross‐sectional, large‐scale study utilizing the computerized data set of Techniker Krankenkasse (TK). TK is the largest statutory health insurer in Germany, providing health insurance for 10.7 million inhabitants nowadays and 8.3 million inhabitants in 2012 17 . Based on the German Social Codebook V, all statutory health insurance companies collect basic data on sociodemographic variables and on comorbidity profile of enrolees 17 .…”
Section: Methodsmentioning
confidence: 99%
“…TK is the largest statutory health insurer in Germany, providing health insurance for 10.7 million inhabitants nowadays and 8.3 million inhabitants in 2012 17 . Based on the German Social Codebook V, all statutory health insurance companies collect basic data on sociodemographic variables and on comorbidity profile of enrolees 17 . All data were fully anonymized by the insurer before they were accessed by the authors.…”
Section: Methodsmentioning
confidence: 99%
“…The C-statistics showed similar discriminatory abilities, i.e., 0.71 (80+ score), 0.57 (STOPP), 0.54 (START), and 0.63 (MAI), demonstrating that all measures had an association with rehospitalization or death. In another study that aimed to internally validate prognostic models to predict health-related quality of life as measured by the EQ-5D-5L, investigators used data from the PRIoritising MUltimedication in Multimorbidity (PRIMUM) cluster randomized controlled trial ( n = 502, ≥60 years, ≥5 drugs, ≥3 chronic diseases) and examined multiple variables in mixed regression models [15]. They found that the MAI score was a significant predictor of health-related quality of life.…”
Section: Validitymentioning
confidence: 99%